Mapping the perception-space of facial expressions in the era of face masks - Verroca, Alessia; de Rienzo, Chiara Maria; Gambarota, Filippo; Sessa, Paola (Frontiers in Psychology, 2022)
With the advent of the SARS-CoV-2 pandemic, the theme of emotion recognition from facial expressions has become highly relevant due to the widespread use of face masks as one of the main devices imposed to counter the spread of the virus. Unsurprisingly, several studies published in the last two years have shown that accuracy in the recognition of basic emotions expressed by faces wearing masks is reduced. However, less is known about the impact that wearing face masks has on the ability to recognize emotions from subtle expressions. Furthermore, even less is known regarding the role of interindividual differences (such as alexithymic and autistic traits) in emotion processing. This study investigated the perception of all the six basic emotions (anger, disgust, fear, happiness, sadness, and surprise) both as a function of the face mask and as a function of the facial expressions’ intensity (full vs. subtle) in terms of participants’ uncertainty in their responses, misattribution errors and perceived intensity. The experiment was conducted online on a large sample of participants (N=129). Participants completed the 20-item Toronto Alexithymia Scale and the Autistic Spectrum Quotient and then performed an emotion-recognition task which involved face stimuli wearing a mask or not and displaying full or subtle expressions. Each face stimulus was presented alongside the Geneva Emotion Wheel (GEW) and participants had to indicate what emotion they believed the other person was feeling and its intensity by means of the GEW. For each combination of our variables, we computed the indices of ‘uncertainty’ (i.e., the spread of responses around the correct emotion category), ‘bias’ (i.e., the systematic errors in recognition) and ‘perceived intensity’ (i.e., the distance from the center of the GEW). We found that face masks increase uncertainty for all facial expressions of emotion, except for fear when intense, and that disgust was systematically confused with anger (i.e. response bias). Furthermore, when faces were covered by the mask, all the emotions were perceived as less intense, and this was particularly evident for subtle expressions. Finally, we did not find any evidence of a relationship between these indices and alexithymic/autistic traits.